Digital Literacy and Career Guidance: A Study on University Students in Indonesia - Muhammad Arif Budiman Sucipto (West Science Social and Humanities Studies, 2024)
In the contemporary landscape of higher education, digital literacy has emerged as a crucial skill set for students, particularly in the realm of career guidance and professional development. This quantitative study aims to explore the relationship between digital literacy and career guidance among university students in Indonesia. By employing a survey methodology, data will be collected from a sample of 300 university students representing various disciplines and academic levels. Statistical analysis, including Structural Equation Modeling with Partial Least Squares (SEM-PLS), will be conducted to examine the extent to which digital literacy influences career guidance practices and career-related outcomes. The findings of this study are expected to contribute to our understanding of the role of digital literacy in shaping career trajectories and inform educational policies and interventions aimed at enhancing students' digital competencies for successful career development.